Scientific interferences in public awareness and health during the pandemic COVID-19 - Mitea , Gabriela; Iancu , Irina Mihaela; Iancu , Valeriu; Erimia , Cristina-Luiza; Schröder , Verginica (Technium BioChemMed, 2023)
The pandemic promoted the need to understand evolutionary principles to solve aspects of human behavior that hinder biomedical innovation and the application of public health services, behaviors that denote insecurity, mistrust and reluctance towards vaccines.Estimating the efficacy of the vaccine (VE) against COVID-19 is essential to assess population protection levels and future booster dose needs to cope with the re-emergence of epidemic waves. This minireview aimed to investigate the relationships between the time course of global SARS-CoV-2 infections (as assessed by case rate and mortality rate) and the development of SARS-CoV-2 vaccination campaigns and post-vaccination follow-up, respectively. The World Health Organization convened the Technical Advisory Group on SARS-CoV-2 Virus Evolution to develop guidance on how best to estimate Strategies for the prevention and control of COVID-19. These detailed overviews of the processes followed, the data used and the methods applied were provided from studies found in the scientific literature.